2022
DOI: 10.3390/jcm11154378
|View full text |Cite
|
Sign up to set email alerts
|

Special Issue: New Insights into the Pathogenesis and Therapies of IgA Nephropathy

Abstract: IgA nephropathy (IgAN) is the most common form of primary glomerulonephritis worldwide [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Furthermore, it can be hypothesized that in the future, these drugs could be used in a synergistic manner so as to target multiple disease pathways. Indeed, these various strategies focus on inhibiting signaling pathways, depleting plasma cells, clearing IgA deposits, modulating mucosal immunity, and blocking complement cascades to treat different aspects of IgAN pathogenesis and progression [13,14].…”
Section: New Drugs For Iganmentioning
confidence: 99%
“…Furthermore, it can be hypothesized that in the future, these drugs could be used in a synergistic manner so as to target multiple disease pathways. Indeed, these various strategies focus on inhibiting signaling pathways, depleting plasma cells, clearing IgA deposits, modulating mucosal immunity, and blocking complement cascades to treat different aspects of IgAN pathogenesis and progression [13,14].…”
Section: New Drugs For Iganmentioning
confidence: 99%
“…IgA nephropathy is characterized by the deposition of IgA immune complexes in the mesangial region of glomeruli, leading to inflammation and progressive fibrosis. The primary clinical manifestation of IgA nephropathy is gross hematuria with or without proteinuria, but it can also produce asymptomatic microscopic hematuria and slowly progressive renal dysfunction (1,2).…”
Section: Introductionmentioning
confidence: 99%
“…Elio G Carmona et al identified a common genetic risk locus for KD and IgAV through a cross-phenotype meta-analysis (Sugiyama et al, 2020). Hitoshi Suzuki et al strongly suggest that IgAN and IgA vasculitis with nephritis (IgA-VN) share similar signs and that galactose deficiency IgA1 plays a very important role in the pathogenesis of both (Suzuki et al, 2018;Suzuki and Novak, 2022). In conclusion, IgAN, IgAV and KD are all immune complex deposition diseases, but in addition, they may be closely related to genetic factors, environmental factors, immune function and other factors that affect the pathogenesis, but it is still unclear at present.…”
Section: Introductionmentioning
confidence: 99%